Exercise Training-induced Modulation in Microenvironment of Rat Mammary Neoplasms - Figueira, Ana Cristina Corrêa; Figueira, Mafalda Corrêa; Silva, Carina; Padrão, Ana; Oliveira, Paula Alexandra; Ferreira, Rita Pinho; Duarte, Jose Alberto (International Journal of Sports Medicine, 2018)
Despite the importance attributed to exercise training in the breast cancer (BC) continuum, the underlying mechanisms modulating tumor behavior are unknown. We evaluated the effects of long-term moderate-exercise in the development of mammary tumors, and studied the microenvironment of infiltrative lesions, the amount of connective tissue, and balance between cellular proliferation/death.Fifty Sprague-Dawley rats, randomly assigned into four groups: two control groups (sedentary and exercised) and two models of BC groups (sedentary and exercised) induced by N-methyl-N-nitrosoureia (MNU), were sacrificed after 35 weeks of moderate-exercise, and all perceptible tumors were removed for histological and immunohistochemistry analysis.The median number of infiltrative-lesions per animal was lower in the MNU exercised animals (p=0.02). More than one histological pattern was identified, and papillary carcinoma was the most frequent in both groups. Within infiltrative-lesions, the number of immunopositive cells per μm2 of Ki67 was lower in exercised animals (p=0.002). This presents increased cell death per μm2 (p=0.019). Tumors from sedentary animals had a higher expression of collagen deposition (p=0.027).Long-term moderate-exercise has beneficial effects in tumor development with a diminished prevalence of malignancy. Within infiltrative-lesions, moderate-exercise improves the balance between cell-proliferation and cell-death with decreased connective tissue that suggests lower tumor aggressiveness.
Keywords: breast tumor; exercise training; ki67; cell death; TUNEL assay; cell proliferation; collagen content